Entomological assessment of the transmission following recrudescence of onchocerciasis in the Comoé Valley, Burkina Faso - Lassane Koala; Achille S. Nikièma; Alain B. Paré; François Drabo; Laurent D. Toé; Adrien M. G. Belem; Daniel A. Boakye; Soungalo Traoré; Roch K. Dabiré (Parasites & Vectors, 2019)
Abstract Background Onchocerciasis, or river blindness, is a dermal filariasis caused by infection with the nematode parasite Onchocerca volvulus, transmitted to humans through the bites of blackflies of the genus Simulium. Despite the decade-long West African Regional Programme for the Elimination of Onchocerciasis, involving the mass administration of ivermectin to populations in endemic areas, recrudescence has occurred. An example is in the Cascades Region of south-west Burkina Faso where the resumption of transmission had resulted in infection prevalences of up to 70% in some villages. In 2011, a strategy for community-directed distribution of ivermectin (CDTI) was set up to respond to this worrying re-emergence. Here, we report on a study of Onchocerca spp. transmission in the affected area carried out from January to December 2012. Every month, host-seeking adult females of the S. damnosum complex were collected at sites on the River Comoé near the four villages (Bodadiougou, Bolibana, Badara Karaboro and Badara Dogossè) that had recorded the highest prevalences in 2010. Collected blackflies were dissected and infective larvae were identified using the O-150 PCR method. Results A total of 9114 S. damnosum (s.l.) adult females were collected, of which 5142 were parous (56.4%) and 78 (1.51%) were infective carrying a total of 137 infective larvae. The annual transmission potential (ATP) was calculated as 0, 30, 255 and 771 infective larvae/man/year in Badara Dogossè, Bolibana, Badara Karaboro and Bodadiougou, respectively. Transmission levels in the latter two are of particular concern as they were higher than 100 infective larvae/person/year, the designated minimum threshold required for elimination of severe pathology, including damage to vision. Conclusions These results confirm that recrudescence of onchocerciasis has occurred, and that transmission of O. volvulus was active at sites on the Comoé River in the Cascades region in 2012. In accordance with WHO recommendations, CDTI should be continued and the situation in the Cascades region should be closely monitored if further spread of this outbreak is to be avoided.